Adsorption and Thermal Evolution of the Carbonyl-functionalized Ionic Liquid [5-oxo-C6C1Im][NTf2] on Pt(111): A Combined IRAS, STM, and DFT Study - Bühlmeyer, Hanna; Knörr, Lukas; Steffen, Julien; Eschenbacher, Roman; Hauner, Jonas; Görling, Andreas; Libuda, Jörg (Chemistry - A European Journal, 2024)
The coating of heterogeneous catalysts with ionic liquids enables precise tuning of catalytic activity and selectivity. Recently, the fundamentals of solid catalysts with ionic liquid layers have been extensively studied. So far, investigations have focused on simple ILs without specialized functional groups. In our current work, we aim to involve functionalized ILs to take advantage of the interactions between these functional groups, the catalyst, and the reactants. In this study, we investigated the interaction, and thermal stability of the carbonyl-functionalized IL [5-oxo-C6C1Im][NTf2] on Pt(111) by infrared reflection absorption spectroscopy and scanning tunneling microscopy. In addition, we performed density functional theory calculations to support our interpretation. At 200 K and low coverage, the carbonyl group of the [5-oxo-C6C1Im]+ cation is oriented parallel to the Pt(111) surface. With increasing coverage, the alkyl chain detaches from the surface and orients towards the vacuum. The [NTf2]− anion adsorbs parallel to the surface via the oxygen atoms of the SO2 groups. At higher coverage, at least one of the SO2 groups completely detaches from the surface. Upon heating to 250 K, we observe decomposition and partial desorption of [5-oxo-C6C1Im][NTf2], with further decomposition and desorption occurring between 350 and 400 K.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Infrared reflection absorption spectroscopy; Ionic liquids; Scanning tunneling microscopy; Pt(111); SCILL

Structure Formation in the Wetting Layer of a Carbonyl-Functionalized Ionic Liquid on Au(111): How to Control the Functional Group? - Knörr, Lukas; Bühlmeyer, Hanna; Steffen, Julien; Trzeciak, Simon; Hauner, Jonas; Zahn, Dirk; Görling, Andreas; Libuda, Jörg (ChemPhysChem, 2025)
Coating heterogeneous catalysts with ionic liquids (ILs), a strategy known as ‘solid catalysts with ionic liquid layers’, can fine-tune catalytic selectivity. Introducing functional groups into ILs enhances their interaction with reactants, but precise control over their positioning is crucial. The structural formation in the IL wetting layer of the carbonyl-functionalized IL [5-oxo-C6C1Im][NTf2] on Au(111) is investigated using infrared reflection absorption spectroscopy and scanning tunneling microscopy under ultrahigh vacuum conditions, supported by density functional theory and molecular dynamics simulations. At low temperatures (<130 K), the IL forms disordered islands, which coalesce into ordered films near ambient temperature. At low coverage, the IL adopts flat, space-demanding adsorption geometries. Upon forming a closed film, adsorption shifts to more compact configurations, with the carbonyl group tilting toward the vacuum while the ring remains surface-bound. Deposition at 300 K forms crystalline structures in the sub-monolayer regime, where the cation side chain can either stand upright or lie flat depending on the coverage. The IL remains thermally stable and desorbs completely at 500 K without decomposition. These findings highlight how IL coverage and deposition conditions tune functional group orientation at the catalyst interface, optimizing SCILL performance.
CRIS-Team Scopus Importer:2025-07-10
Keywords: Au(111); density functional theory; infrared reflection absorption spectroscopy; ionic liquids; molecular dynamics; scanning tunneling microscopy; solid catalysts with ionic liquid layers

Surface Chemistry of a [C2C1Im][OTf] (Sub)Wetting Layer on Pt(111): A Combined XPS, IRAS, and STM Study - Bühlmeyer, Hanna; Talwar, Timo; Eschenbacher, Roman; Barreto, Jade; Hauner, Jonas; Knörr, Lukas; Steinrück, Hans-Peter; Maier, Florian; Libuda, Jörg (ACS Applied Materials and Interfaces, 2024)
The concept of a solid catalyst with an ionic liquid layer (SCILL) is a promising approach to improve the selectivity of noble metal catalysts in heterogeneous reactions. In order to understand the origins of this selectivity control, we investigated the growth and thermal stability of ultrathin 1-ethyl-3-methylimidazolium trifluormethanesulfonate [C2C1Im][OTf] films on Pt(111) by infrared reflection absorption spectroscopy (IRAS) and X-ray photoelectron spectroscopy (XPS) in time-resolved and temperature-programmed experiments. We combined these spectroscopy experiments with scanning tunneling microscopy (STM) to obtain detailed insights into the orientation and adsorption geometry of the ions in the first IL layer. Furthermore, we propose a mechanism for the thermal evolution of [C2C1Im][OTf] on Pt(111). We observe an intact IL layer on the surface at temperatures below 200 K. Adsorbed [C2C1Im][OTf] forms islands, which are evenly distributed over the surface. The [OTf]− anion adsorbs via the SO3 group, with the molecular axis perpendicular to the surface. Anions and cations are arranged next to each other, alternating on the Pt(111) surface. Upon heating to 250 K, we observe changes in geometry and structural distribution. Whereas at low temperature, the ions are arranged alternately for electrostatic reasons, this driving force is no longer decisive at 250 K. Here, a phase separation of two different species is discernible in STM. We propose that this effect is due to a surface reaction, which changes the charge of the adsorbates. We assume that the IL starts to decompose at around 250 K, and thus, pristine IL and decomposition products coexist on the surface. Also, IRAS and XPS show indication of IL decomposition. Further heating leads to increased IL decomposition. The reaction products associated with the anions are volatile and leave the surface. In contrast, the cation fragments remain on the surface up to temperatures above 420 K.
CRIS-Team Scopus Importer:2024-05-10
Keywords: infrared reflection absorption spectroscopy; ionic liquids; Pt(111); scanning tunneling microscopy; SCILL; X-ray photoelectron spectroscopy